Kerangka kerja untuk pengelolaan sumber daya pertanian, kemitraan, peningkatan kesejahteraan dan fasilitasi perluasan lapangan kerja bagi perempuan - Vita Cornelius (Lembaga Administrasi Negara, 2017)
To support economic growth and stability, the development of the agricultural sector is directed at increasing agricultural production and added value, expanding employment opportunities and increasing the income of most members of the community, ie women farmers. By using the above ideas, this paper takes the form of descriptive analysis to find the direction of explanation of the events experienced by the people of Indonesia. Subsequent events are organized into governance frameworks to address the problems occurring in Indonesia. Governments should continue to provide mutual support and engage women's cooperatives for collective decision-making to address unemployment and the poverty line. In addition we can not deny again that with the characteristics of Indonesia is very unique it is necessary role of Food SOEs to exist in the national food management. It takes the scope of cooperation through the MoU in order to benefit both parties in order to meet the regulations in their respective countries as well as to facilitate communication and exchange of information from the governments of both countries.Keywords: village, village administration, Decentralization